2020
DOI: 10.1182/bloodadvances.2020001837
|View full text |Cite
|
Sign up to set email alerts
|

Bridging therapy prior to axicabtagene ciloleucel for relapsed/refractory large B-cell lymphoma

Abstract: Abstract The impact of bridging therapy (BT) administered between leukapheresis and chimeric antigen receptor (CAR) T-cell therapy for large B-cell lymphoma (LBCL) is unclear. We evaluated the influence of BT (systemic therapy [ST], radiation therapy [RT], or combined-modality therapy [CMT]) on outcomes of 148 LBCL patients who underwent leukapheresis for planned axicabtagene ciloleucel (axi-cel) infusion. The 55% (n = 81) of patients who received BT were more li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
143
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(173 citation statements)
references
References 26 publications
6
143
2
1
Order By: Relevance
“…In this issue, Pinnix et al compare the outcomes of 81 patients who received any bridging therapy prior to planned treatment with commercially available axicabtagene ciloleucel to 67 patients who did not. 3 Notably, the patients who received bridging therapy had worse 1-year progression-free survival (PFS) and overall survival than patients who did not. Bridging itself is unlikely to have led to worse outcomes; instead, the patients who needed bridging therapy were likely sicker than those who did not.…”
mentioning
confidence: 99%
“…In this issue, Pinnix et al compare the outcomes of 81 patients who received any bridging therapy prior to planned treatment with commercially available axicabtagene ciloleucel to 67 patients who did not. 3 Notably, the patients who received bridging therapy had worse 1-year progression-free survival (PFS) and overall survival than patients who did not. Bridging itself is unlikely to have led to worse outcomes; instead, the patients who needed bridging therapy were likely sicker than those who did not.…”
mentioning
confidence: 99%
“…Finally, in a phase 2 DLBCL study, BRT patients had higher overall response rate, less severe CRS, and less neurotoxicity compared to chemotherapy‐bridged patients 19 . These results and others suggest that priming with RT may be more effective than chemotherapy 20,21 . Our case differed from those reported in the above series in that our patient was in a clinically precarious situation, and the RT dose given (12 Gy) was selected to produce a local response as a bridge to CAR‐T, but also with the goal of avoiding significant late cardiac toxicity that may have occurred with a more definitive RT dose of 24‐30 Gy.…”
Section: Resultsmentioning
confidence: 57%
“…19 These results and others suggest that priming with RT may be more effective than chemotherapy. 20,21 Our case differed from those reported in the above series in that our patient was in a clinically precarious situation, and the RT dose given (12 Gy) was selected to produce a local response as a bridge to CAR-T, but also with the goal of avoiding significant late cardiac toxicity that may have occurred with a more definitive RT dose of 24-30 Gy. An earlier report showed that there may be a disease control advantage to irradiating all sites of disease prior to CAR-T as compared to only a subset of sites, though it remains unclear whether the potential toxicity of doing so could outweigh this benefit.…”
Section: Debulking and Brtmentioning
confidence: 79%
See 1 more Smart Citation
“…14 Some data suggest that patients who receive bridging therapy while awaiting axi-cel have an outcome inferior to that of patients who do not receive bridging therapy. 10,15,16 Although bridging therapy may have a negative impact, it is more likely that this effect identifies a higher risk group of patients based on the need for disease control after T-cell collection. Theoretically, it is possible that immunosuppressive bridging therapy can enhance CAR-T expansion and persistence.…”
Section: Patient Selectionmentioning
confidence: 99%